The Neuronal Overexpression of Gclc in Drosophila melanogaster Induces Life Extension With Longevity-Associated Transcriptomic Changes in the Thorax - Moskalev, Alexey; Guvatova, Zulfiya; Shaposhnikov, Mikhail; Lashmanova, Ekaterina; Proshkina, Ekaterina; Koval, Liubov; Zhavoronkov, Alex; Krasnov, George; Kudryavtseva, Anna (Frontiers in Genetics, 2019)
Some effects of aging in animals are tissue-specific. In D. melanogaster neuronal overexpression of Gclc increases lifespan and improves certain physiological parameters associated with health benefits such as locomotor activity, circadian rhythmicity and stress resistance. Our previous transcriptomic analyses of Drosophila heads, that are primarily composed of neuronal tissue, revealed the significant changes in expression levels of genes involved in aging-related signaling pathways (Jak-STAT, MAPK, FOXO, Notch, mTOR, TGF-beta), translation, protein processing in endoplasmic reticulum, proteasomal degradation, glycolysis, oxidative phosphorylation, apoptosis, regulation of circadian rhythms, differentiation of neurons, synaptic plasticity and transmission. One of the major diseases of aging is sarcopenia. The purpose of the present study was to investigate the effects of the neuronal Gclc overexpression on gene expression levels in imago thorax, which is primarily composed of muscles. А total of 58 genes were found to be differentially expressed between thoraces of control and Gclc overexpressing flies. Among the functional categories of differentially expressed genes that were overrepresented were Drug metabolism, Metabolism of xenobiotics by cytochrome P450, Glutathione metabolism, Starch and sucrose metabolism, Neuroactive ligand-receptor interaction, One carbon pool by folate, vesicle, Cdc73/Paf1 complex.